2014
DOI: 10.1371/journal.ppat.1004385
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Dependent Enterocyte Invasion and Microcolony Formation by Salmonella

Abstract: The coordinated action of a variety of virulence factors allows Salmonella enterica to invade epithelial cells and penetrate the mucosal barrier. The influence of the age-dependent maturation of the mucosal barrier for microbial pathogenesis has not been investigated. Here, we analyzed Salmonella infection of neonate mice after oral administration. In contrast to the situation in adult animals, we observed spontaneous colonization, massive invasion of enteroabsorptive cells, intraepithelial proliferation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 61 publications
1
92
0
Order By: Relevance
“…Moreover, the majority of the most downregulated genes in 30‐day‐old fetal organoid cultures were similarly expressed in fetal tissue. Additionally, comparison of our fetal organoid dataset to previously published transcription profiles of primary isolated intestinal epithelial cells of neonatal versus adult mice (GEO GSE35596) revealed that 200 upregulated genes in neonatal mouse epithelium were significantly enriched in the fetal organoids cultured for 3 days, whereas 200 downregulated genes correlated with fetal organoids after 30 days of culture (Fig EV1C and D). We next performed Ingenuity Pathway Analyses (IPA) using as input the list of differentially expressed genes between day 3 and day 30 fetal organoid cultures.…”
Section: Resultsmentioning
confidence: 76%
“…Moreover, the majority of the most downregulated genes in 30‐day‐old fetal organoid cultures were similarly expressed in fetal tissue. Additionally, comparison of our fetal organoid dataset to previously published transcription profiles of primary isolated intestinal epithelial cells of neonatal versus adult mice (GEO GSE35596) revealed that 200 upregulated genes in neonatal mouse epithelium were significantly enriched in the fetal organoids cultured for 3 days, whereas 200 downregulated genes correlated with fetal organoids after 30 days of culture (Fig EV1C and D). We next performed Ingenuity Pathway Analyses (IPA) using as input the list of differentially expressed genes between day 3 and day 30 fetal organoid cultures.…”
Section: Resultsmentioning
confidence: 76%
“…In contrast, the neonatal epithelium is largely devoid of mature Paneth cells and expresses the cathelicidin CRAMP . Also, the production of mucins strongly increases with age and so the mucus layer as an additional protective shield only establishes at weaning . Overall, this suggests that a more intense interaction between the microbiota and the host's epithelium occurs in the neonatal host.…”
Section: Postnatal Maturation Of the Neonatal Innate Immune Systemmentioning
confidence: 99%
“…In mice, intestinal epithelial innate immune tolerance is suspended approximately at weaning . Concomitantly, the mucosal barrier is reinforced, illustrated for example by the enhanced mucus production, the appearance of antimicrobial peptides producing Paneth cells, increased TLR3 expression, and the start of the continuous proliferation, crypt–villus axis migration and exfoliation of epithelial cells (Fig. , middle panel).…”
Section: Towards the Concept Of A Temporally Layered Postnatal Establmentioning
confidence: 99%
“…Because of the many similarities in immunity in early life between mice and humans (1, 2), neonatal mice provide a reasonably faithful and experimentally convenient model system for studying infection with bacterial enteropathogens. Indeed, as in humans, mouse neonates are very sensitive to oral infection with a number of bacterial enteropathogens, including Salmonella typhimurium (3, 4), Helicobacter pylori (57), Shigella flexneri (810), Vibrio cholera (11, 12), and the Enteropathogenic E. coli -related Citrobacter rodentium (1316). Often, these susceptibilities are linked to quantitative or qualitative differences in neonatal and adult responses involving both the innate and adaptive gastrointestinal immune systems.…”
Section: Introductionmentioning
confidence: 99%